Molecular Detection of Some Virulence Factors Genes of Proteus Mirabilis That Isolated From Urinary Tract Infection - Afraa Naji Jamel (Journal of Global Pharma Technology, 2016)
A total of (160) clinical specimen of urine collected from patients suffering from urinary tract infections at different ages and from both sex in different hospitals in Baghdad during the period from September 2017 to February 2018.were cultured on selective media MacConkey agar. Bacterial isolates were identified by a microscopic examination and diagnosed by using biochemical tests. A further identification by vitak 2system.The results showed that (103) samples were positive for bacteriological culture (64.6%), the percentage of Proteus spp were (54) urine sample (52.4%) and percentage of Proteus mirabilis isolates were (40) isolates (74%) while Proteus vulgaris were (14) isolates (25.9%) while the results indicated the isolation rate of Proteus mirablis from females was (67%) which was higher than that of males (33%).Selection ten isolates of P. mirabilis which show highest urease activity and adhesion to uroepithelia cell. Aderence capability of the isolates was also tested in accordance to epithelial cells isolated from female urine all isolates were capable of adhering to epithelial cells. The genetic study included an extraction of genomic DNA from (10) p. mirablis, then detection of virulence genes ure C that responsible for urease , mrpA for fimbrial and ability to adherence to uroepithelial cell for these isolated by using convential PCR all isolated give positive result. Selection five from ure c and mrp A gene amplicons of P. mirabilis sent to Korea for direct sequencing. The nucleotide sequences of ure c, and mrp A genes were compared with the sequences of the mrp A and ure c gene using BLAST option of NCBI (Basic Local Alignment Search Tool, BLAST v. 2.2.15, www.ncbi.nlm.nih.gov. The result was 100% matching with the registrar globally.